Malignant hyperthermia in children - Igrutinović Zoran; Vuletić Biljana; Vujić Ana; Marković Slavica; Kostić Gordana (Srpski Arhiv za Celokupno Lekarstvo, 2008)
INTRODUCTION Malignant hyperthermia is a rare disease which is mainly an inherited autosomal dominant trait. It is characteristic for muscle rigidity, metabolism or respiratory acidosis, high values of serum creatine kinase. Then appears myoglobinuria which can lead to tubular necrosis and acute renal failure. CASE OUTLINE The male child, ten years old, hospitalized because of the high temperature, exhaustion and cough. On the second day of hospitalization, he has hyperthermia (39.8°C), dyspnoea, tachypnoea, was somnolent, occasionally raving, exhausted with the pains in the muscles which were rigid and painfully sensitive. During the night, the urine was dark red, but the diuresis was well. The next day, laboratory analyses showed high values of aspartate aminotransferase (4263 IU/l), alanine aminotransferase (1311 IU/l), lactate dehydrogenase (11787 IU/l), while the values of serum creatine kinase were so high that they could not be registered. The urine analysis showed the negative result on gall colours and haematuria and positive on myoglobin. During the following days, the patient had normal skin temperature, the pains in the muscles were gradually weakened and the urine cleared up. On the third day, the value of creatine kinase was measured and it was 178700 IU/l. During the next two weeks, the clinical finding was gradually normalized while the laboratory values of serum enzyme were gradually normalized only in twenty days. CONCLUSION Malignant hyperthermia is a serious clinical syndrome which can be found with, until then, a clinically healthy child (without chronic myopathy) and it appears with the high temperature or during the surgical interventions with anesthetics, which is especially dangerous.